Phenotypic characterization of Landim and Pafúri goat populations in Southern Mozambique based on morpho-structural traits and zoometric indices - Deiby T. Culhe; Matilde F. Matola; Elio Muatareque; Milton P. Morrombe; Matilde A. Manhique; Ramos J. Tseu; Abílio P. Changule; Maria da G. Taela; Custódio G. Bila; Manuel Garcia-Herreros (PLoS ONE, 2026)
This study aimed to characterize the morpho-structural traits of indigenous goats reared at the Chobela Research Station located in Chobela neighbourhood, Magude District, southern Mozambique. A total of 137 goats were selected, comprising 77 Landim and 60 Pafúri animals. Qualitative (morphological) traits were assessed through visual inspection and summarized using frequencies and percentages, while quantitative (morphometric) traits were measured using a zoometric tape and analyzed using analysis of variance (ANOVA) at a 5% significance level. Due to low expected frequencies in some qualitative trait categories, inferential analysis (Chi-square test) was not performed, and these results are presented descriptively. In terms of morphological traits, all Pafúri goats exhibited a convex head profile, whereas Landim goats showed both convex (57.9%) and concave (42.1%) profiles. Approximately 75% of the goats presented a uniform coat colour pattern. Morphometric comparisons based on inferential analysis of female goats (n = 131) due to the limited number of males (n = 6), showed that Landim goats tended to have higher mean values for horn length (19.21 ± 0.83 cm), withers height (58.67 ± 1.20 cm), and body length (67.31 ± 1.73 cm), whereas Pafúri goats exhibited slightly larger head dimensions and thoracic perimeter. However, none of these differences were statistically significant (p > 0.05). Regarding zoometric indices, Landim goats tended to exhibit higher cephalic and thoracic indices, whereas Pafúri goats showed similar or slightly higher body, particularly among females. In contrast, Pafúri goats exhibited marginally higher proportionality indices, reflecting more elongated body proportions. Similarly, the small variations observed in zoometric indices did not reach statistical significance (p > 0.05). We hypothesized that, despite being reared under similar environmental conditions, Landim and Pafúri goat ecotypes would exhibit distinct morpho-structural characteristics due to differences in genetic background and adaptive history. These findings indicate that the morpho-structural differences between the two breeds are mainly descriptive rather than statistically supported. These results provide site-specific and preliminary baseline information for future genetic and phenotypic studies, thus may support conservation and sustainable utilization strategies for indigenous goat populations, particularly those reared under similar management and environmental conditions in southern Mozambique.